Expression of human beta-amyloid peptide in transgenic Caenorhabditis elegans. - Link, C D (1995)
Transgenic Caenorhabditis elegans nematodes have been engineered to express potentially amyloidic human proteins. These animals contain constructs in which the muscle-specific unc-54 promoter/enhancer of C. elegans drives the expression of the appropriate coding regions derived from human cDNA clones. Animals containing constructs expressing the 42-amino acid beta-amyloid peptide (derived from human amyloid precursor protein cDNA) produce muscle-specific deposits immunoreactive with anti-beta-amyloid polyclonal and monoclonal antibodies. A subset of these deposits also bind the amyloid-specific dye thioflavin S, indicating that these deposits have the tinctural characteristics of classic amyloid. Co-expression of beta-peptide and transthyretin, a protein implicated in preventing the formation of insoluble beta-amyloid, leads to a dramatic reduction in the number of dye-reactive deposits. These results suggest that this invertebrate model may be useful for in vivo investigation of factors that modulate amyloid formation.